Edible Vaccines: A Nutritional Substitute for Traditional Immunization - Patel, Prancy; Patel, Riya; Patel, Shivani; Patel, Yukta; Patel, Manan; Trivedi, Riddhi (Pharmacognosy Reviews)
Edible vaccines are created from transgenic plants and animals and contain immunostimulant. Edible vaccines, to put it simply, are medications generated from plants or animals. In underdeveloped countries, oral vaccines are less expensive and more widely available. Researchers came up with the idea of edible vaccines, in which edible plant pieces are employed as a vaccine factory. To make edible vaccinations, scientists put desired genes into plants and then force the plants to generate the proteins expressed in the genes. Transgenic plants are the result of transformation, whereas transformation is the act of converting plants. The edible vaccination promotes mucosal immunity. Dendritic cells in the gut can assist native T cells activate and differentiate into follicular T-helpers (Tfh). T and B cells will respond precisely to a reliable, digestible immunization. Potato, tomato, banana, carrots, tobacco, papaya, algae, and a variety of other plants are utilised as alternative agents for standard vaccinations. Malaria, cholera, hepatitis, rabies, measles, rotavirus, diarrhoea cancer treatments and treatment of covid-19 are among the illnesses for which plant-based vaccines have been created. It takes time and dedication to develop and sell edible vaccinations. Many edible vaccines for animal and human ailments have been developed and have gone through various levels of clinical testing. The importance of plant-based vaccinations is emphasized in this article.
Keywords: Edible vaccine; Transgenic plants; Plant-based vaccine; Infectious diseases; Vaccination